The Contemporary and the Crisis of Empirical Reality: Theoretical Confrontations - Rodríguez Jiménez, Leda (2014)
This article plunges itself into de contemporary to examine its implications by exploring and confronting different theoretical and philosophical positions. Of whom or what are we contemporaneous to? What is the meaning of the concept nowadays? It seems that one of the essential characteristics emerges with and due the unstoppable proliferation of Media. This situation has deeply eroded the concepts of reality and subjectivity. Reality –viewed from the microscope sphere, aesthetic theory in connection with its alleged antithetical pair: fiction- as well as subjectivity –from cogito to the contemporary Media Societies- are all grounds for reflection proposed throughout the article.